A New Tradition (London; Gazelli Art House, 2015)
Gazelli Art House is a contemporary art gallery supporting a wide range of international artists, with exhibition spaces in London and Baku. This publication celebrates the gallery$1 (Bs fifth year in London, and serves as an overview by showcasing an array of works by artists that have exhibited within the gallery$1 (Bs programme since its London debut in 2010. s
English
Keywords: N4390-5098 Visual Arts. Exhibitions; UK